A CURIOUS CASE OF URINARY RETENTION. Issue 10 (9th September 2014) - Lad, Meher; Smith, Matthew; Seth, Jai; Fowler, Clare; Miller, Robert; Panicker, Jalesh
Abstract : A 45 year-old male presented with acute onset urinary retention. 1.8L of urine was catheterised in A&E and he was found to have low grade fever. He was started on ciprofloxacin and an alpha-blocker under the presumptive diagnosis of prostatitis but failed to void after 2 weeks and began reporting sweats and lower back pain. He was diagnosed with Human Immunodeficiency Virus (HIV) infection in the past but was not antiretrovirals; CD4 count was 350 cells/mm 3 and viral load 22, 000 copies/mL. Without a urological cause being established, a neurological review was requested and examination suggested absent third and fourth sacral dermatomal sensations and anal reflex. MRI revealed suspicious enhancement over the lower thoracic cord. CSF protein was 1.44 g/L, glucose 2.3 mmol/l, 62 leukocytes (60% mononuclear), negative acid-fast bacilli, TB PCR and culture, cryptococcal antigen, and viral PCR. CSF HIV viral load was 140, 000 copies/mL. He was started empirically on four-drug anti-tuberculosis regimen and prednisolone. After 6 weeks he began to urinate and discharged without catheter. At 2 months, he reported no voiding difficulties. Urinary retention may occasionally be the only apparent manifestation of an underlying neurological condition. Our patient was found to have chronic meningitis and symptoms improved with treatment.